European agricultural terraces and lynchets: from archaeological theory to heritage management. Issue 4 (7th August 2020) - Brown, Antony; Walsh, Kevin; Fallu, Daniel; Cucchiaro, Sara; Tarolli, Paolo
ABSTRACT: Terraces are highly productive, culturally distinctive socioecological systems. Although they form part of time/place-specific debates, terraces per se have been neglected – fields on slopes or landscape elements. We argue that this is due to mapping and dating problems, and lack of artefacts/ecofacts. However, new techniques can overcome some of these constraints, allowing us to re-engage with theoretical debates around agricultural intensification. Starting from neo-Broserupian propositions, we can engage with the sociopolitical and environmental aspects of terrace emergence, maintenance and abandonment. Non-reductionist avenues include identifying and dating different phases of development within single terrace systems, identifying a full crop-range, and other activities not generally associated with terraces (e.g. metallurgy). The proposition here is that terraces are a multi-facetted investment that includes both intensification and diversification and can occur under a range of social conditions but which constitutes a response to demographic pressure in the face to fluctuating environmental conditions.